2015
DOI: 10.1007/s00132-015-3115-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesie nach Knie-TEP

Abstract: 8,6 ± 2,2 8,0 (7,0-10,0) a 9,0 ± 2,2 8,0 (7,0-10,0) a 8,8 ± 2,2 8,0 (7,0-10,0) a IAK intraartikuläres Kathetersystem, MW Mittelwert, NFK Nervus-femoralis-Katheter, SD Standardabweichung a Median (Interquartilsabstand)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It might be favorably to use a higher dose of LIA to have an immediate effect after surgery. However, compared to other studies the pain relief of the intraarticular analgesia was similar to pain NRS grade 4 on the day of surgery and postoperative day 1 [9,14]. Beyond 24 h, continuous PNB's did not result in superior pain relief.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It might be favorably to use a higher dose of LIA to have an immediate effect after surgery. However, compared to other studies the pain relief of the intraarticular analgesia was similar to pain NRS grade 4 on the day of surgery and postoperative day 1 [9,14]. Beyond 24 h, continuous PNB's did not result in superior pain relief.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies provided no conclusive results for the use of continuous intraarticular analgesia with infusion pumps. While some studies demonstrated the efficacy of continuous intraarticular analgesia [4, 5, 13] other studies did not find a relevant effect [2, 9, 14, 22, 24].…”
Section: Introductionmentioning
confidence: 99%
“…An important point to consider is the different types and concentrations of local anaesthetics used in the studies. The same applies to LIA, where the variety of substances used, their concentrations, volume, and site of application vary widely [ 14 19 ]. Another important point is the type of anaesthesia, where in some studies spinal, general, or both were used [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%